PERENCANAAN DAN PENGENDALIAN UNTUK KREDIT KEMITRAAN DI PT. BANK BUKOPIN CABANG MANADO - Manumpil, Margarietha S. A.; Sabijono, Harijanto; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Banks are institutions that act as financial intermediaries, as a vital means of supporting the smooth running of the economy, in their function of transferring funds from savers or surplus units to borrowing partners or deficit units. Credit control is efforts to keep the credit provided smooth, productive and non-performing. Current and productive means the credit can be withdrawn with interest according to the agreement agreed by both parties. The purpose of this study was to determine the planning and control of partnership credit at PT. Bank Bukopin Manado Branch. And the type of research used is descriptive qualitative approach data, namely data presented descriptively in the form of a description such as the writer's observations during the study in the form of interviews and observations, and presented in the form of data not in the form of numbers. The results showed that credit planning conducted by PT. Bank Bukopin Manado Branch is very well established. This can be seen from the credit budget set from 2017 to 2018 which has increased every year and the implementation of credit control of PT. Bank Bukopin Manado is implemented very well, this can be seen from the targets achieved from 2017 to 2018 experiencing growth every year.